So is There a Place for Morality? A Defence of Jilrgen Habermas's Discourse Ethics. - Faucette, Craig (My University, 2000)
The purpose of this thesis is to offer a defence of Jlirgen Habermas's discourse ethics against rival ethical theories that are oriented toward questions of the good life. Habermas's discourse ethics is founded on the Kantian distinction between the right and good. This distinction has come under fire from hermeneutically informed theorists, such as Georgia Warnke and Charles Taylor, as being either unattainable and unnecessary (Warnke), or contradictory as it must rely on the cultural contextuality in which it is formed (Taylor). But since Habermas's discourse ethics is discursive in nature and founded on the structural pragmatics of language use, it is able to effectively answer both Warnke's and Taylor's concerns. I attempt to prove this by showing that Habermas grounds discourse ethics through linking it with the perspective in which participants partake in actual discourse; thus providing a quasi-contextual basis, while it still remains Kantian in nature, as its scope and function is cognitive, universal and formal.
Keywords: mortality; Jurgen Habermas; ethics; Philosophy; Philosophy